Primary rectal lymphoma with synchronous liver involvement: An extremely rare case report - Kartick Rastogi; Sandeep Jain; Shantanu Sharma; Arpita Jindal (Indian Journal of Medical and Paediatric Oncology)
Both primary rectal lymphoma (PRL) and primary hepatic lymphoma are rare entities, concomitant NHL in rectum and liver is an extremely rare coincidence. Cases of primary colonic lymphoma however can be found in literature. We report an extremely rare case of PRL with synchronous liver involvement after obtaining written informed consent, with a review of available literature. The case was provisionally diagnosed to be an adenocarcinoma of rectum with liver metastasis, with final confirmation on immunohistochemistry. PRL with synchronous liver involvement is an extremely rare coincidence. It is usually confused with more common adenocarcinoma of rectum with liver metastasis posing diagnostic challenges. The optimal management of PRL has never been validated through randomized trials. The treatment options include chemotherapy, radiation, surgical treatment, or a combination of these. Chemotherapeutic agents of choice are the cyclophosphamide, doxorubicin, vincristine, and prednisone regimen, with or without monoclonal antibody rituximab.